Single and Repeated Doses of EGb 761® do not Affect Pharmacokinetics or Pharmacodynamics of Rivaroxaban in Healthy Subjects - Hoerr, Robert; Zimmermann, Andrea; Seitz, Friedeborg; Dienel, Angelika (Frontiers in Pharmacology, 2022)
The present drug-drug interaction study investigates whether single or repeated doses of 240 mg Ginkgo biloba extract EGb 761® alter the pharmacokinetics or pharmacodynamics of rivaroxaban in healthy subjects. This was a single-centre, two-period, fixed-sequence trial. In Period 1, rivaroxaban was taken alone. In Period 2, rivaroxaban was given on the first and last of 8 days of EGb 761® treatment. Plasma concentrations of rivaroxaban and anti-Factor Xa activity were determined until 48 hours after each rivaroxaban intake. The data of forty-one healthy subjects (25 males, 16 females) aged 21 to 70 years were evaluable. Geometric mean ratios (90% confidence intervals) for rivaroxaban administered concomitantly with a single or multiple doses of EGb 761® vs. rivaroxaban administered alone were 97.97 (91.78, 104.58) and 96.78 (90.67, 103.31) for maximum concentration (Cmax), 98.55 (94.43, 102.84) and 97.82 (93.73, 102.08) for area under the concentration-time curve (AUC0-∞) of rivaroxaban in plasma (primary endpoints), 98.19 (92.00, 104.80) and 99.78 (93.43, 106.55) for maximum effect (Emax), 99.46 (93.63, 105.66) and 99.12 (93.25, 105.35) for area under the effect curve (AUEC0-48). All 90% confidence intervals were within the prespecified range of 80% to 125%. Neither adverse events related to haemorrhages nor clinically significant findings in haematology or coagulation parameters were observed. The treatments were safe and well-tolerated. Single and repeated doses of EGb 761® neither affect plasma concentrations of rivaroxaban nor anti-Factor Xa activity in healthy subjects.